PENGARUH DIGITAL MARKETING DAN BRAND IMAGE MELALUI PURCHASE INTENTION TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION NIBRAS HOUSE JOGOROTO - Muhammad Halim Fawazi (STKIP PGRI Situbondo, 2025)
This study investigates the influence of digital marketing and brand image on purchase decisions for Muslim fashion products, with purchase intention serving as a mediating variable. The research aims to determine how digital marketing strategies and brand perception shape consumer decisions in an increasingly competitive Muslim fashion market. Using a quantitative approach and survey data collected from 187 customers of Nibras House Jogoroto, the study applies structural equation modeling with partial least squares to evaluate relationships among variables. The analysis reveals that both digital marketing and brand image significantly influence purchase intention, which in turn strongly predicts actual purchase decisions. However, neither digital marketing nor brand image has a direct effect on purchase decisions, indicating full mediation through purchase intention. These findings highlight the critical role of online engagement, content quality, brand trust, and religious value alignment in shaping consumer intentions toward Muslim fashion products. The study contributes to marketing and consumer behavior literature by demonstrating the dominance of intention-driven pathways in modest fashion purchasing behavior. The results offer strategic implications for industry practitioners